White Racial Activism and Paper Terrorism: A Case Study in Far-Right Propaganda. Issue 2 (1st February 2020) - Castle, Tammy; Kristiansen, Lars; Shifflett, Lantz
ABSTRACT: In 2017, far-right mobilization and demonstrations in the United States were at the highest levels since the 1980s and 90s. This coincided with a marked increase in propaganda campaigns in neighborhoods and across college campuses. Racial activists renewed efforts to rebrand extreme positions, soften racist rhetoric, and grow the movement. The purpose of this case study was to explore the rhetorical content of the propaganda created by one white supremacist. This study contributes to a growing body of literature on far-right propaganda through an examination of common themes, and a comparison of the framing techniques and rhetorical strategies used by other white supremacists.